MODEL PRIORITAS PENINGKATAN KUALITAS SISTEM INFORMASI AKADEMIK MENGGUNAKAN INTEGRASI AHP DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) PADA SMA NEGERI 1 TALAMAU - Afni Nia Sari; Rizalina; Elvira Sawitri (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
The rapid development of information technology has encouraged schools to implement Academic Information Systems (AIS) to improve the effectiveness of academic data management. However, the quality of information system services is often not optimal, resulting in a gap between users' expectations and perceptions. This study aims to determine the priority areas for improving the quality of the Academic Information System at SMA Negeri 1 Talamau through the integration of the Analytical Hierarchy Process (AHP) and Importance Performance Analysis (IPA) methods. The AHP method is employed to determine the priority weights of each system quality criterion, while IPA is used to identify attributes that require improvement based on their importance and performance levels. The study adopts a quantitative approach involving students, teachers, and administrative staff as respondents. The results indicate that the information quality dimension has the highest priority weight, followed by system quality and service quality. The IPA analysis reveals that several attributes fall into Quadrant I (Concentrate Here), making them the main priorities for improvement, particularly regarding system access speed, academic information accuracy, and service responsiveness. This study produces a priority model that can be utilized by the school as a basis for decision-making in enhancing the quality of its Academic Information System.